Mapeamento de minas terrestres por detenção aérea - Rita, Rui Miguel Carapinha (My University, 2024)
The detection of landmines is facing growing challenges due to the evolution of materials used, such as plastics, which reduce the effectiveness of traditional methods. This work aims to develop and integrate technologies that enable landmine detection through the use of unmanned aerial vehicles, in order to improve the identification and localization of buried mines and, consequently, enhancing the safety and efficiency of demining operations. This dissertation begins with a comprehensive literature review on the main landmine detection te chniques. This is followed by a brief analysis of the evolution of unmanned aerial vehicles and their applications in demining, as well as a discussion on the challenges associated with detecting different types of mines in various types of terrain. Themethodologyadoptedfor this study includes defining the necessary hardware and software para meters to optimize landmine detection using Ground Penetrating Radar, developing algorithms to cancel self-interference resulting from the proximity of antennas, and synchronizing the detection systems with the localization module to ensure precise georeferencing of the collected data. The results obtained demonstrate that, despite hardware synchronization issues, the use of unman ned aerial vehicles, self-interference cancellation algorithms, and synchronization between detection and localization allow for greater accuracy in mine detection and georeferencing, especially in hard to-reach or dangerous areas. This system can not only reduce risk for military personnel but also significantly increase the efficiency of demining operations, providing an innovative and safe solution.
Keywords: Radar de penetração no solo; Mapeamento de minas terrestres; Veículos aéreos não tripulados; Cancelamento de auto interferência; Georreferenciação